Economic aspects of caesarean section and alternative modes of delivery (Elsevier, 2001)
Increases in caesarean section rates worldwide have raised questions about the economic implications of caesarean section and alternative modes of delivery. In this chapter, economic aspects of caesarean section and alternative modes of delivery are reviewed and areas where further research is required are identified. The chapter presents the results of a systematic review of the literature and analyses of three large observational data sets. It provides evidence for the cost of labour and delivery, the cost of the postnatal stay and the cost of the long-term health consequences of alternative modes of delivery. The chapter highlights the paucity of methodologically robust economic analyses in this area of health care and concludes that primary research is required to estimate the cost and utilisation of services attributable to caesarean section and alternative modes of delivery. Future research studies should recognise the long-term health service costs and the costs that arise outside the health service, which are likely to vary according to mode of delivery.